2014
DOI: 10.1007/s11684-014-0346-y
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the relationship between plasma lipids and fasting plasma glucose in non-diabetic urban Chinese population: a cross-section study

Abstract: The association between dyslipidemia and elevated fasting glucose in type 2 diabetes is well known. In non-diabetes, whether this association still exists, and whether dyslipidemia is an independent risk factor for high fasting plasma glucose (FPG) levels are not clear. This cross-sectional study recruited 3460 non-diabetic Chinese subjects (1027 men, and 2433 women, aged 35-75 years old) who participated in a health survey. Men and women were classified into tertiles by levels of plasma lipids respectively. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
4
6
1
Order By: Relevance
“…In the current study, although elevated TG levels were more prevalent in men, it was a stronger direct predictor of pre-diabetes in women, a finding that contrasts with previous reports which show that in the pre-diabetic state, high TG and low HDL-C are more prevalent among women compared to men [ 29 , 30 ]; suggesting the presence of a sex-specific underlying mechanism for increasing both TG levels and its different detrimental effects on the progression of pre-diabetes among men and women; these mechanisms may include the effect of female hormones, especially estrogen, on insulin resistance pathways [ 31 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, although elevated TG levels were more prevalent in men, it was a stronger direct predictor of pre-diabetes in women, a finding that contrasts with previous reports which show that in the pre-diabetic state, high TG and low HDL-C are more prevalent among women compared to men [ 29 , 30 ]; suggesting the presence of a sex-specific underlying mechanism for increasing both TG levels and its different detrimental effects on the progression of pre-diabetes among men and women; these mechanisms may include the effect of female hormones, especially estrogen, on insulin resistance pathways [ 31 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In the present group of high cardiovascular risk Thai participants, HDL cholesterol levels in women and men showed opposite directions of association with glycemia, such that, with increasing glycemia, they converged and the well-established advantage of high HDL cholesterol levels in women 30 was eliminated. In the Thai women we studied, HDL cholesterol levels fell with increasing HbA1c, which accords with previously reported observations of the relationship between glycemia and HDL cholesterol across the full range of glycemia; and with the adverse effect of increasing glycemia on the CVD risk profiles being greater in women than in men 31,32 . In men, however, there was a rise in HDL cholesterol levels with increasing FPG, which is contrary to the expected relationship.…”
Section: Discussionsupporting
confidence: 91%
“…Our observations are also consistent with our previous research in a Thai clinical sample at high cardiometabolic risk and with prediabetes defined by FPG and/or HbA1c, which found HDL cholesterol tended to fall with glycemia in women but not in men after taking all relevant factors into account 24 . It also accords with previous clinical studies that have found the adverse effect of increasing glycemia on the CVD risk profiles to be greater in women than in men 25 , 26 .…”
Section: Discussionsupporting
confidence: 91%